Phishing Awareness through Game-Based Learning: A Mobile-Responsive Web Application for Middle School Learners - Uiphanit, Thanakorn; Chutosri, Thatsanan; Wattanaprapa , Natcha; Bunchongkien, Wannarat; Chiewchan, Phachaya; Nachin , Nipon (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study aimed to design a phishing-focused learning approach for middle school learners using a game-based educational format. The objective of this project is to (a) study and develop an educational game to enhance knowledge about phishing emails, (b) compare the academic results before and after learning, and (c) evaluate the acceptability of the educational game to enhance knowledge about phishing emails. The sample group used in this study was 130 from seventh-grade students in School A, Nonthaburi Province, Thailand. To create a game-based learning model focused on phishing emails, the researchers opted for a spot-the-difference game format. The game leveraged the fact that learners were already acquainted with the game’s rules and had prior experience playing it. Furthermore, the game is web-based, enabling learners to engage with it at their convenience, regardless of location or time. The research instruments were (a) a phishing-awareness educational game, (b) preand post-assessment tools to evaluate knowledge gain, and (c) a questionnaire measuring students’ acceptance of game-integrated instruction. The study’s results indicated a high level of learner approval for the phishing-focused instructional model that employed gamified techniques. This acceptance was evident in terms of both the perceived ease of use and the convenience associated with the learning process. Additionally, learners reported significant benefits derived from engaging with the game, including various elements that effectively supported and enhanced their learning outcomes related to phishing emails, resulting in a marked improvement compared to their prior knowledge.